Analysis of Land Acquisition for Yogyakarta International Airport with a Socio-Judicial Approach from an Islamic Law Perspective - Al-Ghazali, Muh. Nurkhalid; Yusdani, Yusdani (Universitas Islam Indonesia, 2023)
The use of land belonging to other people for the public interest is still justified in Islam, of course in a fair and voluntary manner. The land acquisition area for the construction of Yogyakarta International Airport is 637 hectares with 60% of the production land being privately owned by the people and the remainder being Pakualaman Ground. This triggered rejection and even disappointment from residents due to the lack of realization of deliberative agreements. The author examines problems related to the reality of land acquisition for Yogyakarta International Airport using a socio-juridical approach along with the study from an Islamic legal perspective. This qualitative research uses a socio-juridical approach method. The authors combined all primary data in the form of interviews and analyzed it with legal documents related to research material from both legislation and Islamic law. The researcher concluded that land acquisition for the development of Yogyakarta International Airport using a socio-juridical approach has been carried out in stages that uphold the rights of affected residents by considering all possible impacts of land acquisition that will be felt by affected residents, where these stages are appropriate. with statutory law and Islamic law.